Chapter 10: Gender and representation in local politics - Hlynsdóttir, Eva Marín (Edward Elgar Publishing, 2023)
The increased importance of local governance in relation to the provision of welfare services and citizen participation in democratic decision-making has thrust the difference between men's and women's access to positions of authority and power at the local level into the spotlight. In relation to this, the Council of Europe has identified gender equality as a condition for democracy and good governance. This chapter aims to identify the main contemporary discussions on the topic of female descriptive and substantive representation at the local level. The discussion goes beyond the traditional Western approach and draws from multiple sources from different regions throughout the world, thus shedding light on the international differences and similarities of the effect of local politics on gender representation. The chapter offers comprehensive, up-to-date information on the topic, introducing this much-needed area of research to students and academics for further investigation.